Muscle oxygenation, heart rate, and blood lactate concentration during submaximal and maximal interval swimming - Dalamitros, A. A.; Semaltianou, E.; Kabasakalis, A. (Frontiers in Sports and Active Living, 2021)
This study aimed to determine the relationship between three testing procedures during different intensity interval efforts in swimming. Twelve national-level swimmers of both genders executed, on different occasions and after a standardized warm-up, a swimming protocol consisting of either a submaximal (Submax: 8 efforts of 50 m) or a maximal interval (Max: 4 efforts of 15 m), followed by two series of four maximal 25 m efforts. Near-infrared spectroscopy in terms of muscle oxygen saturation (SmO2), heart rate (HR), and blood lactate concentration (BLa) were analyzed at three testing points: after the Submax or the Max protocol (TP1), after the 1st 4 × 25-m (TP2), and after the 2nd maximal 4 × 25-m set (TP3). BLa and HR showed significant changes during all testing points in both protocols (P = 0.01; ES range: 0.45-1.40). SmO2 was different only between TP1 and TP3 in both protocols (P = 0.05-0.01; ES range: 0.36-1.20). A large correlation during the Max protocol between SmO2 and HR (r: 0.931; P = 0.01), and also between SmO2 and BLa was obtained at TP1 (r: 0.722; P = 0.05). A range of moderate-to-large correlations was revealed for SmO2/HR, and BLa/HR for TP2 and TP3 after both protocols (r range: 0.595-0.728; P = 0.05) were executed. SmO2 is a novel parameter that can be used when aiming for a comprehensive evaluation of competitive swimmers' acute responses to sprint interval swimming, in conjunction with HR and BLa.